Processamento simbólico arquetípico: uma proposta de método de pesquisa em psicologia analítica - Penna, Eloisa Marques Damasco (2009)
The objective of this study was to propose a research method for analytical psychology and for such an investigation was undertaken into the academic production in analytical psychology doctorate thesis and masters dissertations at two Brazilian universities PUC-SP and USP from 2002 through 2007. The material collected was analyzed based on the methodological guidelines for the Jungian paradigm. The analysis of the research projects identified the main methodological procedures adopted by the researchers, both for collecting and for interpreting the data, and the articulation between the objective of the research, the phenomenon selected as the object of research and the methodological procedures used to collect and analyze the material; the most frequent research modules were identified together with the main difficulties faced by the researchers in undertaking their research. Based on an analysis of the material collected, a research method for investigation into analytical psychology was proposed. The research process, within the Jungian paradigm, includes stages for apprehending and comprehending phenomena, during which methodological procedures and resources are used that are compatible with the basic guidelines for the paradigm, which include symbolic amplification. Special attention was given to the researcher s participation in the process, considering his/her function and academic background and more importantly, the development of a symbolic attitude to approach the work and within the relationship researcher-researched . This research also identifies the main risk that the research activity presents to the contemporary Jungian researcher, and consequently, the care that needs to be taken during the research process. Finally, the ethical implications of scientific activity in general are discussed, and particularly in the work of Jungian researchers. The research method in analytical psychology, given its characteristics, epistemology and methodologies, is referred to as an archetypical symbolic procedure